Letting the daylight in: Reviewing the reviewers and other ways to maximize transparency in science - Wicherts, Jelte M.; Kievit, Rogier A.; Bakker, Marjan; Borsboom, Denny (Frontiers in Computational Neuroscience, 2012)
With the emergence of online publishing, opportunities to maximize transparency of scientific research have grown considerably. However, these possibilities are still only marginally used. We argue for the implementation of (1) peer-reviewed peer review, (2) transparent editorial hierarchies, and (3) online data publication. First, peer-reviewed peer-review entails a community-wide review system in which reviews are published online and rated by peers. Reviewers with higher average ratings are weighted more heavily in publication decisions, thereby ensuring academic quality of reviews. Second, reviewers who write many highly regarded reviews may move to higher editorial positions. This leads to a transparent basis for editorial hierarchies and prevents politically inspired editorial appointments. Third, online publication of data ensures the possibility of independent verification of inferential claims in published papers. This counters statistical cherry-picking and data massaging to obtain favorable results. We illustrate the benefits of these strategies by discussing an example in which the classical publication system has gone awry, namely controversial IQ research. We argue that this case would have likely been avoided using more transparent publication practices. We argue that the proposed system leads to better reviews, meritocratic editorial hierarchies, and a higher degree of replicability of statistical analyses. Therefore it leads to a publication system that more fully benefits from the advantages and possibilities offered by online, open access publication.